Primary angioplasty for infarction due to isolated right ventricular artery occlusion - Chahal, Anwar A (World J Cardiol, 2014)
We report an unusual case of an isolated right ventricular infarction with haemodynamic compromise caused by spontaneous isolated proximal occlusion of the right ventricular branch of the right coronary artery (RCA), successfully treated by balloon angioplasty. A 58-year-old gentleman presented with epigastric pain radiating into both arms. Electrocardiograph with right ventricular leads confirmed ST elevation in V4R and a diagnosis of isolated right ventricular infarction was made. Urgent primary percutaneous intervention was performed which revealed occlusion of the right ventricular branch of the RCA. During the procedure, the patient’s blood pressure dropped to 80/40 mmHg, and echocardiography showed impaired right ventricular systolic function. Despite aggressive fluid resuscitation, the patient remained hypotensive, continued to have chest pain and persistent electrocardiograph changes, and hence balloon angioplasty was performed on the proximal right ventricular branch which restored flow to the vessel and revealed a severe ostial stenosis. This was treated with further balloon angioplasty which restored TIMI 3 flow with resolution of patient’s symptoms. Repeat echocardiography showed complete resolution of the ST-elevation in leads V4R and V5R and partial resolution in V1. Subsequent dobutamine-stress echocardiography at 4 wk showed good left and right ventricular contractions. The patient was discharged after a 3-d in-patient stay without any complications.